Crescimento inicial e desempenho agronômico de cultivares norte-americanas de cártamo - Maziero, Claudia Luiza (2019)
Safflower cultivars may be cultivation options because of the limited improvement in cultivars commercially grown and registered in Brazil. The objective of this work was to evaluate the initial growth and agronomic performance of North American safflower cultivars in Brazil. The experiment was carried out at the CDTER - Center for Technological Development and Dissemination in Renewable Energies, at Fundetec in Cascavel-PR, in a randomly distributed Oxisol with six (C1, C2, C3, C4, C5, C6) and six replicates. At 15 DAE (days after emergence), the emergency percentage, the emergency speed index, the mean germination time and the mean emergency speed were determined. At 30 DAE, the height of the plants and the diameter of the stem, the number of leaves per plant, as well as the fresh and dry mass of the plant. At flowering, plant height, stem diameter, number of branches and number of chapters were determined. At harvest, the final population of plants, grain yield and mass of chapters, weight of 100 grains, oil content and protein were determined. The cultivar C1 stood out in relation to the initial growth, with greater emergence and rate of emergency speed. At 30 days after emergence the cultivars did not differ in relation to the accumulation of dry mass and number of leaves. During flowering, the cultivars C6 and C3 presented greater accumulation of dry mass of plant and root, besides a greater number of leaves, branches and chapters. Cultivars C5 and C4 presented higher grain yield, while cultivars C2 and C6 had higher oil content and cultivar C1 had higher protein content.